Universal dimensions of individuals' perception: Revisiting the operationalization of warmth and competence with a mixed-method approach - Halkias, Georgios; Diamantopoulos, Adamantios (International journal of research in marketing, 2020)
A dynamic and growing body of marketing literature draws from the Stereotype Content Model's (SCM) dimensions, warmth and competence, to describe individuals' perception of various market-related stimuli (e.g., salespeople, employees, products) and predict their influence on subsequent behavior. However, the operationalization of these fundamental dimensions in empirical marketing research has been inconsistent and problematic, hindering comparability of findings across studies and limiting the overall usefulness of warmth–competence in relevant research. Using a mixed-method approach, the present paper scrutinizes the warmth–competence dimensions in order to validate and optimize their measurement. Through seven studies using different methodologies and metrics, we identify a set of trait items that (a) capture perceptions of warmth and competence consistently across a variety of impression formation settings, and (b) display strong psychometric properties. Our findings offer a parsimonious approach that promotes the consistent operationalization of warmth and competence across marketing studies and enables the integration of empirical findings, both of which are crucial requirements for meta-analytic investigations, replication studies, and integrative reviews. •Researchers increasingly rely on the dimensions of warmth and competence to study market-related phenomena.•Shortcomings in the development of these dimensions lead to inconsistent applications, reducing their theoretical and practical relevance.•Using diverse methods and metrics we identify a parsimonious set of items that consistently capture warmth–competence perceptions.•Findings promote the systematic operationalization of warmth–competence across studies, enabling meta-analytic investigations, replication studies, and integrative reviews.